SOME OUTLOOKS ON CREATIVITY IN MATHEMATICS TEACHING - Hariz Agić; Sead Rešić (Human Research in Rehabilitation, 2015)
The role and significance of Mathematics in human life is very important and holds a special place in development of contemporary society. Creativity in Mathematics teaching largely depends on Mathematics teacher. Teacher is the one who creates emotional environment in the classroom and it is expected from him/her to create with the students a relationship of trust and mutual responsibility for the success of conducting the teaching process. Students need to be interested and activated to individually solve tasks and find solutions to set Mathematical problems, to solve tasks in different ways using various methods, so that everybody can find a way of coming to a solution. This is easy to say. In any case, creativity as a competence holds a significant place in the set of key life competencies. Only teachers can answer questions whether Mathematics classes are creative, interesting, or acceptable for students. This paper will contain certain theoretical viewpoints about creativity in general, creative Mathematics teaching, relation towards creativity at school and outside. Research has shown that examinees (teachers of class and subject teaching in elementary and secondary schools) believe that they did not receive a good background during their university studies for strengthening teaching creativity. It transpired that creativity, as opposed to student and teacher, is appreciated less at the school and education system levels. Teachers (of all levels) have shown high level of agreement regarding the need for turnover in relation to creativity in Mathematics teaching, which would guarantee increase of interest of students for Mathematics.